THE INCREASING IMPORTANCE OF CIVIL SOCIETY ORGANIZATIONS IN SHARING THE SOCIAL ASSISTANCE RESPONSIBILITY OF PUBLIC ADMINISTRATION: THE EXAMPLE OF SAÇAKLIZADE FOUNDATION (Third Sector Social Economic Review, 2024)
The aim of this study, which analyses the social assistance services of the Saçaklızade Foundation, is to draw attention to the potential of NGOs in Türkiye to provide social assistance based on the activities of the foundation, and to discuss the importance and necessity of these structures in sharing the social aid responsibility of the public administration. While the main data source of the study was semi-structured interviews with the foundation officials, the foundation's annual reports were another important data source that enriched the study quantitatively. In the study, it was observed that the foundation continued its activities even in global and regional disasters such as the Covid-19 pandemic and 6 February 2023 Kahramanmaraş Earthquakes, that there was no concern about the interruption of social assistance services due to the presence of people who would continue this service voluntarily, and that reliability is a sine qua non condition for the sustainability of social assistance services. In addition, in order to more clearly reveal the potential of organizations carrying out social assistance activities in Kahramanmaraş, the data shared by 5 social assistance organizations has become another important source that enriches the content of the study. In the study, it has been seen that public institutions were supported and acted jointly in ordinary and extraordinary periods. It has been concluded that food banks, soup kitchens and education aids have undertaken important tasks in sharing the social assistance responsibility of the public administration. It has also been concluded that there is a lack of specialisation in food bank services due to the insufficient number of employees and excessive workload and that there is a need for a new soup kitchen to operate in the city centre.
Keywords: Public Administration; Non-Governmental Organisation; Social Assistance; Saçaklızade Foundation; Kahramanmaraş